Exogenous Hormonal Application Regulates the Occurrence of Wheat Tillers by Changing Endogenous Hormones - Cai, Tie; Meng, Xiangping; Liu, Xiaoli; Liu, Tiening; Wang, Hui; Jia, Zhikuan; Yang, Dongqing; Ren, Xiaolong (Frontiers in Plant Science, 2018)
Plant hormones play important roles in regulating the occurrence of crop tillers. However, little is known about the relationships and the underlying mechanisms between endogenous hormones and the occurrence of wheat tillers induced by exogenous hormones. In this study, two winter wheat cultivars, Xinong 979 and Xiaoyan 22, were used to investigate the effects of the exogenous application of indole-3-acetic acid (IAA) and zeatin (Z) on the occurrence of wheat tillers and investigate underlying mechanisms regulating the occurrence of tillers. The results showed that the application of IAA inhibited the occurrence of tillers, and external Z application promoted the occurrence rate of tillers under low nitrogen conditions. Further analysis of the results showed that exogenous IAA completely inhibited the growth of tiller buds, while exogenous Z significantly promoted the growth rate of tiller buds in low nitrogen conditions. Endogenous hormones exhibit important functions in regulating the growth of tiller buds, which contents were affected by exogenous hormones. Furthermore, according to the principal component analysis (PCA) and correlation analysis, the growth of tiller buds was significantly positively correlated with the content of endogenous Z, whereas it was significantly negatively correlated with the ratios of endogenous IAA to endogenous Z (IAA:Z) and endogenous abscisic acid (ABA) to endogenous Z (ABA:Z). Moreover, no significant correlation was observed between the growth of the tiller buds and the endogenous IAA, endogenous gibberellins (GAs), and endogenous ABA content. These results suggested that Z played key roles in regulating the tiller occurrence, and exogenous hormones regulated the growth of wheat tiller buds via affecting the Z contents, thus regulating the occurrence of wheat tiller.